The Impact of Digital Marketing, Financial Literacy, And Digital Literacy on Purchasing Intent for Online Products - Cahyono, Tomy Dwi; Rizqi, Reza Muhammad (Indonesian Business Review, 2024)
The swift advancement of technology has greatly influenced how humans engage with technology, leading to fundamental changes in communication and transactions. This has led to substantial prospects for the expansion of e-commerce in Indonesia. This study aims to elucidate the impact of digital marketing, financial literacy, and digital literacy on online product purchasing decisions. This study utilized an associative quantitative method utilizing structural equation modeling-partial least square (SEM-PLS). The study employed purposive sampling to choose a sample of 100 students from the Faculty of Economics and Business at Sumbawa University of Technology. Data is collected through a questionnaire distributed using a Google Form. The study shows that digital marketing, financial literacy, and digital literacy have a partial impact on the interest in purchasing things online. This highlights the significance of employing efficient digital marketing methods and consumers' comprehension of finance and information technology to enhance their inclination towards purchasing things online. Companies can boost their sales by prioritizing the enhancement of digital literacy and marketing expertise.